Youth Creativity Media Empowerment Through Social Media Content Creator - Sirmayanti Sirmayanti; Mahjud I; Puspita I; Mahyati M; Rizal M; Hasanah U; Mujahida N; Yusrianto Y; Fadli MN; Rahman F; Adil N (International Journal Of Community Service, 2022)
Generations of Millennial, X, Y and Z are very synonymous with social media presence. More focus on Generation Z which in fact were born in an era that is surrounded by cyberspace with Internet facilities, cellular technology and digital technology that are connected stable. PKM partners are students of MAN 3 Makassar and GMA-community to carry out optimization of science and technology applications through content creators with social media platforms so that Islamic da'wah media is more widespread and affordable to all people. The main target of partners is the digital natives of the Gen-Z. They are the GMA-community Mosque Youth Association which their number are 30% of the community population. The types of PKM activities are learning-by-project-based training and coaching graphic design & video-image editing to target partners so that new skills are formed in the creativity of da'wah content on the created social media platforms. The results of the technology transfer that have been provided are content creator training and the creation of 5 YouTube, Instagram, Facebook, Spotify and Web media accounts equipped as account administrator for managing social media and image and video products of the Islamic da'wah content.